ANALISIS KONTRASTIF KONSTRUKSI PASIF BAHASA JAWA KUNA DAN BAHASA JAWA (STUDI KASUS PRASASTI HARIÑJIŊ) - Churmatin Nasoichah; nfn Mulyadi (Forum Arkeologi, 2019)
Passive sentence is a sentence subject to accept or subject to action. There are two languages which also have passive sentences, namely Javanese and Old Javanese. Before the Javanese language developed, it was known as Old Javanese. Old Javanese as one of the derivatives of Austronesian languages is a language that has very old literature. By studying the Hariñjiŋ A, B, C Inscriptions as one of the proofs of the use of Old Javanese language, the research was carried out with contrastive analysis, namely comparing it with Javanese. The problem is how do passive constructs in Old Javanese language (the case study of Hariñjiŋ A, B, CInscriptions) and Javanese when viewed using contrastive analysis? The purpose is to describe passive construction in Old Javanese (a case study on the Hariñjiŋ A, B, C Inscriptions) and Javanese inscriptions and compare the two sentence patterns. The method of this research is descriptive qualitative by using a descriptive comparative contrast method which aims to provide an overview of passive sentences and find differences. The conclusions are that the construction of passive sentences in Old Javanese (in the writing of the Hariñjiŋ A, B and C Inscriptions) has a transitive passive and intransitive passive form which is the same as Javanese. The passive form is indicated by a kiks prefix, a combination of affix-in, a combination of affixes, a combination of ma-affixes, and infix -in-. Whereas the Javanese language is only known to be a prefix, di- -ni, and di-confix, or to be deunned. It can be concluded also that passive sentence Javanese is not derived from Old Javanese but rather has an influence from Malay which is the forerunner of Indonesian. Kalimat Pasif merupakan sebuah kalimat subjek menerima atau dikenai aksi. Terdapat dua bahasa yang juga memiliki bentuk kalimat pasif, yaitu bahasa Jawa dan bahasa Jawa Kuna. Sebelum bahasa Jawa berkembang, telah dikenal adanya bahasa Jawa Kuna. Bahasa Jawa Kuna sebagai salah satu turunan dari bahasa Austronesia adalah bahasa yang mempunyai kesusastraan yang sangat tua. Dengan mengkaji Prasasti Hariñjiŋ A, B, C sebagai salah satu bukti adanya penggunaan bahasa Jawa Kuna, penelitian dilakukan dengan analisis kontrastif yaitu membandingkannya dengan bahasa Jawa. Adapun permasalahannya adalah bagaimanakah konstruksi pasif pada bahasa Jawa Kuna (studi kasus Prasasti Hariñjiŋ A, B, C) dan bahasa Jawa apabila dilihat dengan menggunakan analisis kontrastif? Adapun tujuannya untuk mendeskripsikan konstruksi pasif dalam bahasa Jawa Kuna (studi kasus pada Prasasti Hariñjiŋ A, B, C) dan bahasa Jawa serta membandingkan kedua pola kalimat tersebut. Metode penelitian ini bersifat deskriptif kualitatif dengan menggunakan metode deskriptif komparatif kontras yang bertujuan memberikan gambaran tentang bentuk kalimat pasif serta menemukan perbedaannya. Adapun kesimpulannya adalah konstruksi kalimat pasif dalam bahasa Jawa Kuna (dalam penulisan Prasasti Hariñjiŋ A, B, dan C) memiliki bentuk pasif transitif dan juga pasif intransitif yang sama dengan bahasa Jawa. Bentuk pasifnya ditandai dengan prefiks ka-, kombinasi afiks -in- -an, kombinasi afiks -in- -akan, kombinasi afiks ma- -akĕn, dan infiks -in-. Sedangkan bahasa Jawa hanya diketahui prefiks di-, konfiks di- -ni, dan konfiks di- -ne, atau dipun- -aken. Dapat disimpulkan juga bahwa kalimat penanda pasif bahasa Jawa bukan diturunkan dari bahasa Jawa Kuna melainkan mendapat pengaruh dari bahasa Melayu yang merupakan cikal bakal bahasa Indonesia.